PEMAHAMAN KETERAMPILAN HASIL BELAJAR PESERTA DIDIK TINGKAT SEKOLAH MENENGAH ATAS PADA MATERI MEMANDIKAN, MENGKAFANKAN DAN MENSHOLATKAN JENAZAH - Muhammad Ali Akbar; Itsolendra Itsolendra (Program Pascasarjana IAIN Langsa, 2020)
This article discusses the obligation of Muslims when someone dies, is to take care of the body. The law is fardhu kifayah, which means an obligation if there is already a group of people who take care of the body, starting from bathing, forgiving, praying, burying, other Muslim obligations will fall. The law of fardhu kifayyah is associated with high school student education, which becomes concentrated in understanding the skills of high school student learning outcomes.